An Assessment of Farmers' Associations in Western Leyte, Philippines - Dagoy, Salvador C. (1985)
The main purpose of this study was to assess Farmers' Associations in western Leyte, Philippines in terms of six viability indicators and six membership behavior factors. The specific objectives were: (1) to assess Farmers' Associations, in terms of six viability indicators, (2) to ascertain differences among Farmers' Associations in terms of six membership behavior factors, and (3) to determine problems of the Farmers' Associations as perceived by the members. Data collected from 120 members of the eight Farmers' Associations were analyzed using the following SPSS subprograms.